Expectations of Majlis Amanah Rakyat (MARA) stakeholders on the Ulul Albab curriculum at a MARA Junior Science College (MRSM) - Abdul Manaf, Umi Kalthom; Alias, Nurul Fitriah; Nor Azman, Ady Hameme; Abd Rahman, Fadzilah; Zulkifli, Hafizah (Australian International Academic Centre, 2014)
Ulul Albab is an educational programme of integration between the existing programmes in MARA Junior Science College (MRSM) with the religious school programme including Tahfiz Al-Quran. MRSM Ulul Albab education programme is designed to produce professional experts, entrepreneurs and technocrats that are well versed in the field of religion-based Al-Quran and Sunnah as Ulul Albab generation. This study aims to explore stakeholders' expectations on the Ulul Albab programme in MRSM Kota Putra, Besut Terengganu towards students' sahsiah. The methodology used was qualitative in nature in the form of semi-structured interviews conducted with the four MARA stakeholders. Validity and reliability of data were done through several techniques employed such as member checking, rich thick description, clarification of researcher biases, peer review and debriefing, and external audit. The findings from this study indicate that inculcation of akhlak is fundamental in human capital development. This is the case because stakeholders believe that the main intention of the programme is to develop an Ulul Albab generation who are not only knowledgeable and skilled but also possess good qualities namely devotion, noble, responsible and committed to religion, nation and state. Aside from that, findings also showed that teaching and learning that is based on love is fundamental in fostering good akhlak.